2011
DOI: 10.4028/www.scientific.net/msf.702-703.730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn on <100> Texture Evolution in Fe-Si-Mn Alloys

Abstract: The texture can be evolved through the γ to α transformation by cooling in Fe-Si alloy systems. Oxygen in the annealing atmosphere hampers the evolution of the texture. The texture evolution is associated with the fact that the {100} faces are elastically compliant so that the texture can develop in a manner consistent with minimization of strain energy. By alloying Mn to Fe-Si alloys, the texture evolves in relatively high oxygen containing annealing atmosphere. The role of Mn in the texture evolution appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Although <100> orientation is the soft crystallographic direction with lowest elastic modulus in the BCC Fe, {100} α ‐phase grains may lose the primary condition of growth advantage due to surface oxidation. Sung et al pointed out that the cube faces are elastically compliant so that the texture can develop in a manner consistent with minimization of strain energy and the oxides at the metal surface will modify the elastic anisotropy and curb the development of {100} texture, clean metal surface was a necessary condition for the preparation of strong {100} transformation texture. When the hydrogen flow rate is low, α ‐phase grains formed preferentially at the sheet surface do not have enough driving force to grow inwards, and the thin layer of {100}<011> grains induced by surface effect is finally retained, whereas the texture components in the center layer inherit the recrystallization {111} textures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although <100> orientation is the soft crystallographic direction with lowest elastic modulus in the BCC Fe, {100} α ‐phase grains may lose the primary condition of growth advantage due to surface oxidation. Sung et al pointed out that the cube faces are elastically compliant so that the texture can develop in a manner consistent with minimization of strain energy and the oxides at the metal surface will modify the elastic anisotropy and curb the development of {100} texture, clean metal surface was a necessary condition for the preparation of strong {100} transformation texture. When the hydrogen flow rate is low, α ‐phase grains formed preferentially at the sheet surface do not have enough driving force to grow inwards, and the thin layer of {100}<011> grains induced by surface effect is finally retained, whereas the texture components in the center layer inherit the recrystallization {111} textures.…”
Section: Resultsmentioning
confidence: 99%
“…Among the electrical steels processed by phase transformation method, the mediate level of Si content of about 1% is more difficult to deal with and less investigated. Only Sung et al processed successively the Fe–1Si alloy and Xie et al prepared successively Fe–0.7Mn–1.28Si–0.07C. In this work, we tried to prepare full columnar grained structure and improved textures in the Fe–0.82Si–1.37Mn electrical steels using surface effect induced transformation method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many reports on the preparation of favorable {100} texture in low‐grade electrical steel by phase transformation annealing. [ 4–13 ] However, the effect of structures’ inhomogeneity on phase transformation has been rarely reported. [ 14 ] The study by Gu et al [ 15 ] has shown that the five different initial structures prepared by columnar grains have a noteworthy effect on phase transformation texture after phase transformation annealing, and meanwhile, the texture memory phenomenon appears during phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports on the phase transformation treatment during final annealing to obtain the favorable {100} columnar grain structure in non-oriented electrical steel. [1][2][3][4][5][6][7][8][9][10][11] Moreover, the textural memory phenomena of phase transformation, the K-S orientation relationship and the variant selection phenomena have also been widely observed in various steels, [12][13][14][15][16][17][18][19][20] and the mechanism of their formation is considered to be based on grain boundary nucleation and double K-S (Kurdjumov-Sachs) relationship. [20][21][22][23] However, it is rarely reported how to retain {100} textures in hot rolled sheets.…”
Section: Introductionmentioning
confidence: 99%